DIGGING FROZEN GROUND - Sergeev,A. I. (1961)
The following methods of trench construction in frozen ground were investigated: (1) utilization of a disk saw in both vertical and horizontal positions; (2) utilization of drop hammers as pressure cutters and of wedges to dispose of the blocks produced; (3) cutting narrow channels in the frozen ground 3-4 cm wide using a 12-bladed cutter; (4) utilization of a modified trench excavator with a chain conveyor. The first two methods were judged useless. The third method required minimum power, but a high rate of blade damage and wear rendered it impracticable. The fourth method was also hampered by a high rate of blade wear and, in addition, had a high power consumption. Possible schemes for overcoming the blade-wear problem are discussed. Razrabotka Merzlykh Gruntov, trans. of Mekhanizatsiya Stroitelstva (USSR) v13 n1 p6-10 1956.